PENTINGNYA MENGUTAMAKAN KESEJAHTERAAN MENTAL SISWA BAGI PUNCAK PENCAPAIAN PEDAGOGIS - S, Sanusi (EDUCHILD (Journal of Early Childhood Education), 2023)
Mental well-being has emerged as a paramount concern in today's educational framework. Even though academic development is a primary focus, students' emotional and psychological stability holds equal significance. Studies indicate that a notable percentage of the youth grapple with mental challenges, with many not accessing the necessary care, which in turn affects their educational journey. The roles of educators and parents are instrumental in providing this essential support. However, various hurdles, such as limited resources, societal misconceptions, and communication gaps, hinder the implementation of robust mental health initiatives in educational settings and homes. Nevertheless, with strategic training, strengthened collaboration between institutions and families, and supportive policies, It is possible to create a supportive learning environment that prioritizes and improves students' overall wellbeing.